Effects of Sodium and Amino Acid Substrate Availability upon the Expression and Stability of the SNAT2 (SLC38A2) Amino Acid Transporter - Hoffmann, Thorsten M.; Cwiklinski, Emma; Shah, Dinesh S.; Stretton, Clare; Hyde, Russell; Taylor, Peter M.; Hundal, Harinder S. (Frontiers in Pharmacology, 2018)
The SNAT2 (SLC38A2) System A amino acid transporter mediates Na+-coupled cellular uptake of small neutral α-amino acids (AA) and is extensively regulated in response to humoral and nutritional cues. Understanding the basis of such regulation is important given that AA uptake via SNAT2 has been linked to activation of mTORC1; a major controller of many important cellular processes including, for example, mRNA translation, lipid synthesis and autophagy and whose dysregulation has been implicated in the development of cancer and conditions such as obesity and type 2 diabetes. Extracellular AA withdrawal induces an adaptive upregulation of SNAT2 gene transcription and SNAT2 protein stability but, as yet, the sensing mechanism(s) that initiate this response remain poorly understood although interactions between SNAT2 and its substrates may play a vital role. Herein, we have explored how changes in substrate (AA and Na+) availability impact upon the adaptive regulation of SNAT2 in HeLa cells. We show that whilst AA deprivation induces SNAT2 gene expression, this induction was not apparent if extracellular Na+ was removed during the AA withdrawal period. Furthermore, we show that the increase in SNAT2 protein stability associated with AA withdrawal is selectively repressed by provision of SNAT2 AA substrates (Me-AIB and glutamine), but not non-substrates. This stabilization and substrate-induced repression was critically dependent upon the cytoplasmic N-terminal tail of SNAT2 (containing lysyl residues which are putative targets of the ubiquitin-proteosome system), because “grafting” this tail onto SNAT5, a related SLC38 family member that does not exhibit adaptive regulation, confers substrate-induced changes in stability of the SNAT2-5 chimeric transporter. In contrast, expression of SNAT2 in which the N-terminal lysyl residues were mutated to alanine rendered the transporter stable and insensitive to substrate-induced changes in protein stability. Intriguingly, SNAT2 protein stability was dramatically reduced in the absence of extracellular Na+ irrespective of whether substrate AAs were present or absent. Our findings indicate that the presence of extracellular Na+ (and potentially its binding to SNAT2) may be crucial for not only sensing SNAT2 AA occupancy and consequently for initiating the adaptive response under AA insufficient conditions, but for enabling substrate-induced changes in SNAT2 protein stability.